Vore gamle tropekolonier..? – Tropekolonierne som danske erindringssteder - Andersen, Astrid Nonbo (Slagmark - Tidsskrift for idéhistorie, 2018)
The knowledge of the Danish colonial past has for a very long time played a minor role in the general picture of Danish History in Denmark. Within the past 10-15 years however the former Danish tropic colonies in the West Africa, East India and the West Indies have attracted a growing number of Danish visitors in search for the colonial past. This has led to a number of renovation projects sponsored by Danish agents in collaboration with the local authorities in the former tropic colonies. This article takes its analytical starting point in the French Historian Pierre Nora’s notion of places of memory (lieux de mémoire) and deals with some of the problems of both a philosophical and political kind that spring from these new initiatives.